An Explicit Isomorphism in $\mathbb{R}/\mathbb{Z}$-K-Homology - Elmrabty, Adnane; Maghfoul, Mohamed (Communications in Mathematics and Applications, 2014)
In this paper, we construct an explicit isomorphism between the at part of differential K-homology and the Deeley $\mathbb{R}/\mathbb{Z}$-K-homology.